Student protagonism and the challenges of contemporary society: a dialogue on the project of life (Research, Society and Development, 2022)
This article presents the results of a research that aims to understand whether the development of an individual life project can contribute to the student participation of high school youth and adolescents. The study considers aspects such as autonomy, protagonism, engagement, responsibility, of young people facing the challenges of contemporary society. This study was structured based on the answers obtained through a questionnaire applied to 21 high school students. This investigation takes on a qualitative character, based on Content Analysis procedures. However, the information collected was also interpreted quantitatively. High School students who reflect on their life project have positively developed characteristics in terms of engagement, dedication, motivation, attitude towards daily life, identity formation. There is no exact moment for the individual to take direction in life, but a delay in choosing one can lead to giving up in the search for positive paths, lack of goals, lack of commitment to a professional career, life, family.